WAYS OF USING MNEMONICS IN TEACHING NEW VOCABULARY TO PUPILS (Scientific journal of the Fergana State University, 2023)
In the article were analyzed ways using mnemonics in teaching new vocabulary. Ways of teaching new vocabulary trough interesting types of scripts, graphemes and pictures are given.